2020
DOI: 10.18860/mec-j.v4i3.8203
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing Tools, Religiosity, Environmental Attitude And Green Purchase Behaviour Among Millenials Generation

Abstract: The purpose of the research isto examine relationship between Green Marketing Tools (GMT), Environmental Attitudes (EA), Religiosity and Green Purchase Behavior (GPB) and test Religiosity moderates between Environmental Attitudes (EA) and Green Purchase Behavior (GPB). This study employs samples using a questionnaire instrument. The result of the collected 268 questionnaires of respondents were processed using descriptive and quantitative analysis data using SEM (Strutural Equation Model) analysis techniques w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The next study from (Solekah et al, 2020) with the results of research Green behavior is influenced by individual factors such as religious and situational factors, green marketing tools, green labels, green label beliefs, financial or green labels and brands, and environmental promotions, with recommendations Behavioral analysis related to technology development. Psychological aspects can be used for further research, the next study Behavioral analysis related to technology development.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next study from (Solekah et al, 2020) with the results of research Green behavior is influenced by individual factors such as religious and situational factors, green marketing tools, green labels, green label beliefs, financial or green labels and brands, and environmental promotions, with recommendations Behavioral analysis related to technology development. Psychological aspects can be used for further research, the next study Behavioral analysis related to technology development.…”
Section: Research Resultsmentioning
confidence: 99%
“…Green marketing as a concept with business is proven in the presentation delivered with the results of research which is also submitted to dozens of scientific articles such as from (A. ; (Arli &;Tjiptono, 2017), (Chung, 2020), (Szabo &;Webster, 2021), (Solekah et al, 2020), (Tanwari, 2020), (Khan et al, 2020), (Al-Majali &;Tarabieh, 2020 ), (Shabbir et al, 2020) and . Some of the results of the research above are related to this research by proving and corroborating the truth that the concept of green marketing has been used in various business organizations with various gaps and phenomena.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…According to Garzella and Fiorentino [17], the impact of green management policies is related to four dimensions, namely 1) environmental strategy formulation in the form of integrating the legitimacy and the significance of the biophysical environment into the strategic process formulation; 2) synchronization of environmental strategies and practices in the form of implementation processes; 3) achievement of environmental results in the form of actual performance and the impact of strategic measures on the biophysical environment; 4) finance and competitiveness in the form of the impact of better environmental processes on earnings, costs, and competitive advantage. Some research on green management including Asni and Agustia [18], that focus on green innovation, another research discusses about corporate governance and green innovation [19], green market orientation and supply chain management [20][21][22] green technology and supply chain [23,24] green marketing and supply chain [25].…”
Section: Green and Sustainability Management In Smesmentioning
confidence: 99%
“…Green product listing tries to address all the credible and easily readable information related to environmental safety (Amankwah-Amoah, 2020) states that product listing is an essential and worth considering tool to overcome the pressure of competitors and strengthening the relationship between a product and a customer (Ariffin et al, 2019;Amankwah-Amoah, 2020). Previous studies found that if we add an environment friendly effect to our product listing, it will automatically manipulate the mindsets and behaviour of the consumers (Solekah et al, 2020). They discussed that this thing works as a great marketing tool, but there is a need to share the importance of environment friendly products and their distinct features, which make them superior over regular products (Ezzati, 2021).…”
Section: Product Listingmentioning
confidence: 99%